Synthesis, Photophysical and Electrochemistry of Near-IR Absorbing Bacteriochlorins Related to Bacteriochlorophyll a - Kozyrev, Andrei (2012)
A series of new bacteriochlorins was synthesized using 13(2)-oxobacteriopyropheophorbide- a (derived from bacteriochlorophyll-a) as a starting material, which on reacting with o-phenylenediamine and 1,10-diaminonaphthalene afforded highly conjugated annulated bacteriochlorins with fused quinoxaline, benzimidazole and perimidine rings respectively. The absorption spectra of these novel bacteriochlorins demonstrated remarkably red-shifted intense Q(y) absorption bands observed in the range of 816–850 nm with high molar extinction coefficients (89,900–136,800). Treatment of 13(2)-oxo-bacteriopyropheophorbide a methyl ester with diazomethane resulted in the formation of bacterioverdins containing a fused six member methoxy substituted cyclohexenone (verdin) as an isomeric mixture. The pure isomers which exhibit long wavelength absorptions in the near-IR region (865–890 nm) are highly stable at room temperature with high reactivity with O(2) at the triplet photoexcited state, favorable redox potential and could be potential candidates for use as photosensitizers in photodynamic therapy (PDT).